The correlation of dentin elastic moduli and pH after exposed to combination of calcium hydroxide-propolis-propylene glycol - Ira Widjiastuti; Fauziah Diajeng Retnaningsih; Yashinta Ramadhinta; Salsabila Nunki Widona; Sukaton (Wolters Kluwer Medknow Publications, 2022)
Previous research states that adding propolis to powdered dental materials can increase the mechanical strength of the material. To analyze the differences and correlation of dentin elastic moduli and pH value after the exposure of calcium hydroxide, a mixture of propolis and calcium hydroxide, also a mixture of propylene glycol (PG), calcium hydroxide, and propolis. The dentine of bovine incisors was exposed into various compositions of a mixture of propolis, PG, and calcium hydroxide. The measurement of pH value and dentin elasstic moduli was performed after 7 days. To find difference among groups, one-way ANOVA was used, and Honestly significant difference (HSD) Tukey to compare each groups, followed by Pearson to define the correlation. A statistically meaningful difference was recorded between the groups (P < 0.05), and there was correlation between dentin elastic moduli and pH value. The more alkaline the environment, the more rigid the dentin.